Killer cell immunoglobulin-like receptor genotypes in the Turkish population - (:unkn) unknown (ELSEVIER SCIENCE INC, 2018)
One hundred eighty-seven healthy and unrelated volunteers from various regions of Turkey were selected for the study. Killer-cell immunoglobulin-like receptors (KIR) genotyping was performed by polymerase chain reaction using commercial sequence-specific oligonucleotide probe (SSOP) kits. Gene frequencies of the Turkish population were determined by direct counting of the positive and negative loci. The genotype data is publicly available in the Allele Frequencies Net Database under the population name Turkey KIR pop 3 number 3399.